Fabrication of a co-culture micro-bioreactor device for efficient hepatic differentiation of human induced pluripotent stem cells (hiPSCs). (5th November 2018) - Kehtari, Mousa; Zeynali, Bahman; Soleimani, Masoud; Kabiri, Mahboubeh; Seyedjafari, Ehsan
Abstract: Primary hepatocytes, as the gold standard cell type for in vitro models, lose their characteristic morphology and functions after few days. There is an urgent need to develop physiologically relevant models that recapitulate liver microenvironment to obtain mature hepatocyte from stem cells. We designed and fabricated a micro-bioreactor device mimicking the physiological shear stress and cell–cell interaction in liver sinusoid microenvironment. Induced pluripotent stem cells (iPSCs) were co-cultured with human umbilical vein endothelial cells (HUVECs) in the micro-bioreactor device with continuous perfusion of hepatic differentiation medium (100 μL/h). Simulation results showed that flow field inside our perfusion device was uniform and shear stress was adjusted to physiological condition (<2 dyne/cm 2 ). IPSCs-derived hepatocytes (iPSCs-Heps) that were cultured in micro-bioreactor device showed a higher level of hepatic markers compared to those in static condition. Flow cytometry and immunocytochemistry analysis revealed iPSCs cultured in the device sequentially acquired characteristics of definitive endodermal cells (SOX17 positive), hepatoblasts (AFP positive) and mature hepatocyte (ALB positive). Moreover, the albumin and urea secretion were significantly higher in micro-bioreactor device than those cultured in culture dishes during experiment. Thus, based on our results, we propose our micro-bioreactor as a beneficial device to generate mature hepatocytes for drug screening and basic research.